Vulnerability to acid reflux of the airway epithelium in severe asthma. Issue 2 (4th August 2022) - Perotin, Jeanne-Marie; Wheway, Gabrielle; Tariq, Kamran; Azim, Adnan; Ridley, Robert A.; Ward, Jonathan A.; Schofield, James P.R.; Barber, Clair; Howarth, Peter; Davies, Donna E.; Djukanovic, Ratko
Background: Severe asthma is associated with multiple comorbidities, including gastro-oesophageal reflux disease (GORD), which can contribute to exacerbation frequency and poor quality of life. Since epithelial dysfunction is an important feature in asthma, we hypothesised that in severe asthma the bronchial epithelium is more susceptible to the effects of acid reflux. Methods: We developed an in vitro model of GORD using differentiated bronchial epithelial cells (BECs) from normal or severe asthmatic donors exposed to a combination of pepsin, acid pH and bile acids using a multiple challenge protocol (MCP-PAB). In addition, we analysed bronchial biopsies and undertook RNA sequencing of bronchial brushings from controls and severe asthmatics without or with GORD. Results: Exposure of BECs to the MCP-PAB caused structural disruption, increased permeability, interleukin (IL)-33 expression, inflammatory mediator release and changes in gene expression for multiple biological processes. Cultures from severe asthmatics were significantly more affected than those from healthy donors. Analysis of bronchial biopsies confirmed increased IL-33 expression in severe asthmatics with GORD. RNA sequencing of bronchial brushings from this group identified 15 of the top 37 dysregulated genes found in MCP-PAB treated BECs, including genes involved in oxidative stress responses. Conclusions and clinical implication: By affecting epithelial permeability, GORD may increase exposure of the airway submucosa to allergens and pathogens, resulting in increased risk of inflammation and exacerbations. These results suggest the need for research into alternative therapeutic management of GORD in severe asthma. Using a combination of in vitro and ex vivo approaches, this study identified reflux causing significant effects on the bronchial epithelial structure and function, which were greater in patients with severe asthma https://bit.ly/31XV9tq